INTEGRASI MAQASHID SYARIAH DAN SGDS DALAM MODEL PEMBIAYAAN MIKRO SYARIAH KONTEMPORER - fatkhullah, imam; zen, muhammad (JSE: Jurnal Sharia Economica, 2026)
This study aims to analyze the relevance of maqasid al-shariah in microfinance through a comparative dialogue between classical fiqh and the practices of contemporary Islamic Microfinance Institutions (IMFIs). Using a qualitative descriptive-comparative approach based on library research, the study examines classical sources such as al-Ghazali, al-Syatibi, and Ibn ‘Ashur, alongside modern literature on Islamic microfinance. The findings reveal that classical fiqh emphasizes normative protection of the five essential dimensions of maqasid through simple contracts such as qardh, mudharabah, and musyarakah. In contrast, contemporary IMFIs apply maqasid in a more practical manner, focusing on financial inclusion, economic empowerment, and sustainable development. The study also identifies challenges in consistent implementation due to limited resources and market competition, yet highlights opportunities through innovative Islamic financial instruments and the legitimacy of DSN-MUI fatwas. Thus, maqasid al-shariah can be viewed as a dynamic framework that balances shariah compliance with socio-economic welfare, positioning IMFIs as agents of just, inclusive, and sustainable transformation.